Upaya Penggunaan Metode Telemetri untuk Penelitian Berang-Berang Cakar Kecil (Aonyx cinereus) di Area Persawahan - Mahfud Huda; Jabang Nurdin; Wilson Novarino; Hanif Fadly; Aadrean Aadrean (Jurnal Biologi Universitas Andalas, 2017)
Currently, telemetry appeared as a common method to reveal home range and movement of animal. However, the telemetry method was not applied for small-clawed otter yet. We have spent efforts to use the telemetry methods from March to August 2016 in a rice field landscape in Lubuk Alung district, Padang Pariaman regency, West Sumatra. We trapped individuals of small-clawed otters (Aonyx cinereus) using leg-hold traps and box traps. We implanted radio transmitter intraperitoneally. Movement of the animal was recorded using triangulation methods. Two male individuals of small-clawed otters were captured. One individual died soon after the transmitter implantation and another individual was successfully implanted and released. However the individual were detected for 28 hours only. In this paper, we described the efforts and problems appeared from the trapping, transmitter implantation, releasing and radio tracking process.